A novel PSMA-targeting tracer with highly negatively charged linker demonstrates decreased salivary gland uptake in mice compared to [68Ga]Ga-PSMA-11 - Steve S. Huang; Frank P. DiFilippo; Daniel J. Lindner; Warren D. Heston (SpringerOpen, 2024)
Abstract Background The current generation of radiolabeled PSMA-targeting therapeutic agents is limited by prominent salivary gland binding, which results in dose-limiting xerostomia from radiation exposure. JB-1498 is a urea-based small molecule with a highly negatively charged linker targeting prostate specific membrane antigen (PSMA). Prior work on a similar tracer with the same negatively charged linker demonstrated low normal organ/soft tissue background uptake compared to [68Ga]Ga-PSMA-11. The purpose of this study was to investigate if [68Ga]Ga-JB-1498 had reduced salivary gland uptake in mice compared to [68Ga]Ga-PSMA-11. Results JB-1498 demonstrated high affinity for PSMA binding and tumor uptake in a murine tumor model. In an initial biodistribution study with low molar activity, [68Ga]Ga-JB-1498 demonstrated salivary gland uptake of 0.13 ± 0.01%ID/g. In a second biodistribution study in non-tumor-bearing mice with high molar activity, [68Ga]Ga-JB1498 demonstrated salivary gland uptake of 0.39 ± 0.24% ID/g and kidney activity of 10.12 ± 1.73% ID/g at one hour post IV injection. This salivary gland uptake is significantly less than the published uptake of [68Ga]Ga-PSMA-11. Micro-PET visually confirmed the findings of the biodistribution studies. Dynamic micro-PET imaging demonstrated gradually decreasing [68Ga]Ga-JB1498 activity in salivary glands and kidneys, compared to gradually increasing [68Ga]Ga-PSMA-11 activity in these two organs during the first hour. Conclusion Biodistribution and micro-PET imaging of [68Ga]Ga-JB-1498 demonstrate significantly decreased salivary gland uptake and different pharmacokinetic behavior in kidneys and salivary glands in mice compared to [68Ga]Ga-PSMA-11. Our findings suggest that constructing a PSMA-targeting molecule with a highly negatively charged linker is a promising strategy to reduce salivary gland uptake of GCP-II/PSMA ligands in theranostic applications.